2005
DOI: 10.1111/j.1468-2478.2005.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality and Intrastate Armed Conflict

Abstract: In this article, I examine to what extent gender equality is associated with lower levels of intrastate armed conflict. I use three measures of gender equality: (1) a dichotomous indicator of whether the highest leader of a state is a woman; (2) the percentage of women in parliament; and (3) the female-to-male higher education attainment ratio. I argue that the first two measures in particular capture the extent to which women hold positions that allow them to influence matters of war and peace within a state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 230 publications
(181 citation statements)
references
References 40 publications
6
172
0
3
Order By: Relevance
“…Previous research has established that the level of gender equality within a country correlates to the peacefulness of the state (Caprioli 2005, Melander 2005, Hudson et al 2009, Gleditsch et al 2011, Reiter 2014. This study provides unique micro-level evidence that links misogynist attitudes with self-reported participation in political violence among political activists.…”
Section: Resultsmentioning
confidence: 67%
“…Previous research has established that the level of gender equality within a country correlates to the peacefulness of the state (Caprioli 2005, Melander 2005, Hudson et al 2009, Gleditsch et al 2011, Reiter 2014. This study provides unique micro-level evidence that links misogynist attitudes with self-reported participation in political violence among political activists.…”
Section: Resultsmentioning
confidence: 67%
“…iv The data on armed conflict comes from the UCDP/PRIO Armed Conflict Dataset (www.ucdp.uu.se), presented in Gleditsch et al 2002. v This interaction effect was theoretically deduced and empirically corroborated by Melander (2005a) .…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, when militarized masculinity is strongly present it is likely that violence is viewed as an acceptable means of imposing and maintaining domination. The more widespread and pervasive militarized masculinity is, the more likely it is that conflict will be dealt with violently ( Pin-Fat and Stern 1992, 2005, Enloe 1993, Gibson 1994, Gill 1997, Kimmel 1997, Fone 2000, Hooper 2000, Caprioli 2000, 2005, Goldstein 2001, Tickner 2001, Micheler 2002, Kimmel and Mahler 2003, Melander 2005a, 2005b ii .…”
Section: Political Gender Equality and Civil Peacementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Melander (2005) emphasizes the commonality between gender roles that legitimize the subordination of women and the dominant warlike role of men (see also Goldstein 2001;Caprioli 2000). Since the emergence of more equal gender roles also strengthens norms of respect and individual inviolability, and extend social norms that reject abuse and violence to a wider sphere, higher gender equality should be associated with less collective violence, including both civil war and interstate war.…”
Section: Polygyny Legal Polygamy and Civil Warmentioning
confidence: 99%